2008
DOI: 10.1002/bjs.6082
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase signalling mediates endotoxin hypersensitivity after partial hepatectomy

Abstract: Hepatectomy increased susceptibility to LPS by Rho-kinase-dependent mechanisms. Blocking Rho-kinase signalling decreased LPS-induced liver injury in hepatectomized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…[11][12][13] Fasudil (1-[5-isoquinolinesulphonyl]-homopiperazine), a ROCK inhibitor, has been widely used clinically since 1995 for the treatment of subarachnoid haemorrhage in Japan.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…[11][12][13] Fasudil (1-[5-isoquinolinesulphonyl]-homopiperazine), a ROCK inhibitor, has been widely used clinically since 1995 for the treatment of subarachnoid haemorrhage in Japan.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Notably, Rho-kinase inhibitors have been demonstrated to ameliorate reperfusion and endotoxemic injury in the liver [20] as well as protecting against tissue fibrosis [21], obstructive cholestasis [22], intestinal ischemia [23] and pulmonary hypertension [24]. Previous studies have shown that CXC chemokine formation in acute pancreatitis [25], colonic ischemia-reperfusion [23] as well as cholestatic [22] and endotoxemic [20] liver injury is regulated by Rho-kinase. However, the role of Rho-kinase signaling in regulating CXC chemokine formation, neutrophil recruitment and tissue edema in M1 protein-induced acute lung injury is not known.…”
Section: Introductionmentioning
confidence: 99%
“…By now, Y-27632 is a well established pharmacological agent to analyze the involvement of Rho-kinase in the pathogenesis of various diseases [25]. Our present findings now add cholestatic liver injury to the list of diseases in which Rho-kinase appears to regulate tissue damage, including ischemiareperfusion damage of the liver [17] and heart [26], septic liver injury [16,18], cerebral ischemia [27,28], and pulmonary hypertension [29].…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the Rho/Rhokinase pathway has been implicated in several inflammatory processes, such as chemokine expression and leukocyte-endothelial cell interactions [15,16]. Accordingly, inhibition of Rho-kinase has been shown to be effective against liver injury in models of ischemiareperfusion [17] and sepsis [16,18] as well as carbon tetrachloride-induced hepatic fibrosis [19] and cell death [20]. However, the potential role of Rho-kinase in cholestasis-induced inflammation in the liver remains elusive.…”
Section: Introductionmentioning
confidence: 98%